How Do Central Banks Control Inflation? A Guide for the Perplexed - Castillo-Martinez, Laura; Reis, Ricardo (Journal of Economic Literature, 2026)
Central banks have a primary goal of price stability. They pursue it using tools that include the interest they pay on reserves, the size and the composition of their balance sheet, and the dividends they distribute to the fiscal authority. We describe the economic theories that justify the central bank’s ability to control inflation and discuss their relative effectiveness in light of the historical record. We present alternative approaches as consistent with each other, as opposed to conflicting ideological camps. While interest-rate setting may often be superior, having both a monetarist pillar and fiscal support is essential, and at times pegging the exchange rate or monetizing the debt is inevitable. (JEL E31, E43, E52, E58, E62, F31, G21)